Effect of Some Nutritional Supplements and Treatments Taken by Pregnant Women on the Health of the Children after Birth - Jaythoom, Roaa A. (American Journal of Biology and Natural Sciences, 2026)
Background: We conducted this study to evaluate the effects of treatments taken by mothers during pregnancy on the child during pregnancy or after birth. On the other hand, the current study may contribute to raising awareness to avoid taking medications that pose a risk to the child’s stages of development before or after birth. Method: The current study is a cross-sectional study that included collecting a questionnaire and medical examinations from 100 mothers with their children suffering from health problems that related to the treatments that the mother took during pregnancy. Examinations were performed for the mother and child, which included routine tests, diagnostic tests, hormonal tests, and Ultrasound. Result: The children's ages ranged from 1 day – 10 years, with an average age of 1.32 months. Current study showed that most children born to a mother who used medication during pregnancy suffer from breathing disorders resulting from lung disorders as asthma (22%). We also found that (13%), (10%), (11%), and (8%) of the children suffer from speech problems, incomplete growth (premature birth), mental problems, and vision problems respectively. We found that blood pressure medications that mothers took during pregnancy had the greatest role in the occurrence of heart disease, epilepsy, paralysis, and premature birth of babies while pregnancy stabilizers led to the emergence of many health problems in children, especially lung disorders such as asthma, digestive system disorders, delayed speech, and brain dysfunction. Moreover, taking antibiotics during pregnancy was associated with the appearance of jaundice, epilepsy, and abnormal tooth development in children after birth. Furthermore, treatments for gestational diabetes have led to the emergence of many diseases in children, the most important of which are polio, type 1 diabetes, and growth problems. In conclusion: UTI, blood pressure, anemia, and gestational diabetes are the most common pregnancy health problems in our society, the treatment of which directly or indirectly causes a deterioration in the health condition of the fetus during pregnancy and may extend for years after birth.